The Effect of Competency, Motivation and Work Discipline on Employee Performance of PT. Buana Samudera Lestari - Meiana Kusuma Astuti; Istiatin; Ida Aryati P.W (Institute of Computer Science (IOCS), 2021)
The running of human resources is very influential on the progress of the company. By preparing resources that are able to meet the needs of a quality company. This study aims to test competence, motivation, work discipline on employee performance at PT. Buana Samudera Lestari. Determination of the sample technique of incidental sampling with a population of 2300 using the Slovin formula obtained 100 samples with multiple linear regression calculation method. The results of the study Fcount> Ftable (18.494> 2.70) and sig. 0.000 <0.05, competence, motivation, work discipline simultaneously have a significant effect on employee performance at PT. Buana Samudera Lestari. Partially the competency value of tcount> ttable (3,217> 1,985) and sig. 0.002 <0.05 competence has a positive and significant effect on employee performance at PT. Buana Samudera Lestari. The motivation for the value of tcount> ttable (6,014> 1,985) and sig. 0.000 <0.05 motivation has a positive and significant effect on employee performance at PT. Buana Samudera Lestari. Work discipline tcount> ttable (2,668> 1,985) and sig. 0.009 <0.05, work discipline has a positive and significant effect on employee performance at PT. Buana Samudera Lestari Employee performance can serve by three independent variables by 48.5% and the others, yes by other variables.